The toucan in early modern French culture (1526-1650) - Lawrence, A (2023)
This is a thesis about the life of a strange little bird in early modern European culture. Bright and colourful in feather yet bizarre in physical form, bearing a seemingly impossible bill, the Toucan inspired wonder in many a traveller to the New World. Transcribed into text, it soon appeared in books of several genres, in the drawings of artists and, as a material sample, in the cabinets de curiosités of collectors and dignitaries. The sheer breadth of source material available indicates the cultural significance of the Toucan; our discussion sets out to assess the bird's impact on early modern thought and culture.